Current-mode universal filters using unity-gain cells - Abuelma’atti, M.T. (1996)
Two new current-mode universal filters are presented. The proposed filters use unity gain current and voltage followers. The first filter has three inputs and one output and can realise lowpass, highpass and bandpass responses without any changes in the circuit topology. Realisation of notch and allpass responses can be easily achieved without adding any additional active elements. The second filter has three inputs and one output and can simultaneously realise lowpass, highpass and bandpass responses without any changes in the circuit topology. Realisation of notch and allpass responses can be easily achieved without adding any additional active elements. The proposed circuits enjoy low active and passive sensitivities